Role of Strategic Investment Approaches on Efficient Performance of Real Estate firms in Kenya - Achieng, Olivia Adhiambo; Mule, Robert Kisavi; Aila, Fredrick Onyango (European Scientific Journal, ESJ, 2022)
Resources like time, organizational efforts and materials require efficient management in order to achieve greater outputs. Every organization need to reduce waste in these resources to the minimum possible so as to produce high quality services and products. The real estate industry has been evolving overtime from the traditional conventional bricks and mortar industry to be more dynamic and operational, focusing on access and outcomes rather than ownership. Investors who do not develop creative and cost-effective strategies of accessing operational experience and innovation are likely to have diminishing returns on their investments. This paper illustrates how efficiency in operations is influenced by how investors select a combination of their investment portfolio. The study reviews and analyses the concept of operational efficiency of real estate investment firms in Nairobi county and suggests ways in which it can be improved in future through strategic decision making. This article sought to establish the effect of strategic investment approaches on efficient performance of real estate investment firms in Kenya, the study period being 2018-2022. Strategic investment approaches were the independent variable and efficient performance the dependent variable thus analyzing the relationship between the two variables. Theoretical literature links strategic investment approaches to investment performance both positively and negatively with some scholars stating that there is a positive relationship between the two while other scholars contradicting. Correlational survey design and census sampling method were used to draw 231 registered real estate investment firms in Kenya’s capital city of Nairobi. Primary data was gathered using structured questionnaires to collect data from 231 operations managers and analyzed by regression analysis. The findings of the study indicated that strategic investment approaches is positively correlated to efficient performance at (p<0.05) and R² of 60.3% indicating that 60.3% change in efficient performance is caused by strategic investment approaches while 39.7% will be explained by other factors. The study revealed that strategic investment approaches is a strong driver of operational efficiency thus recommends that the firm’s strategic intelligence teams should proactively integrate strategic innovation and move away from the old ways of creating and managing real estate.